Assessing the Compatibility of Brussels I Regulation with Kosovo’s Private International Law - Mehmeti, Sami; Elezaj, Granit (Acta Universitatis Danubius. Juridica, 2025)
This paper assesses the compatibility between the Brussels I Regulation and the Kosovo Private International Law. Brussels I regulates jurisdiction and the recognition and enforcement of judgments in civil and commercial matters in the European Union. Conversely, Kosovo adds an extra level of complexity into the mix. An independent country since 2008, Kosovo has since sought European Union membership. As such, harmonization - the process of aligning national laws with EU legal and regulatory standards that Kosovo has committed to — is of utmost importance, not simply in terms of legal formalism, but also to illustrate the strategic imperative of the need to align such legislation for the purposes of advancing Kosovo on its path towards the EU. This paper provides an in-depth analysis of the current frameworks, delineating how to rectify differences and suggesting approaches for alignment and integration. It gives insight into two fundamental elements of the two legal instruments, namely, jurisdictional rules and the protection of weaker parties. The jurisdictional rules section examines the regulations basing competence on the defendant’s domicile or habitual residence. It also covers related claims, counterclaims, jurisdictional anchors like the defendant’s assets and provisional measures. It explicitly addresses the discrepancy between Kosovo’s official recognition process and the EU’s principle of automatic recognition.